Сlinical and radiology assessment of pneumonias in desomorphin drag patients - M. Yu. Chupanova; A. I. Mandel; T. S. Ageyeva; V. D. Zawadovskaya; I. M. Semenyuk; V. N. Korenyugina (Бюллетень сибирской медицины)
Peculiarities of clinical progression and X-ray pattern of inflammatory lung changes in patients having five-month to two-year long desomorphine addiction are described based on clinical and X-ray analysis of 187 patients with desomorphine addiction.